Iron, anemia and hepcidin in malaria - Spottiswoode, Natasha; Duffy, Patrick E.; Drakesmith, Hal (Frontiers in Pharmacology, 2014)
Malaria and iron have a complex but important relationship. Plasmodium proliferation requires iron, both during the clinically silent liver stage of growth and in the disease-associated phase of erythrocyte infection. Precisely how the protozoan acquires its iron from its mammalian host remains unclear, but iron chelators can inhibit pathogen growth in vitro and in animal models. In humans, iron deficiency appears to protect against severe malaria, while iron supplementation increases risks of infection and disease. Malaria itself causes profound disturbances in physiological iron distribution and utilization, through mechanisms that include hemolysis, release of heme, dyserythropoiesis, anemia, deposition of iron in macrophages, and inhibition of dietary iron absorption. These effects have significant consequences. Malarial anemia is a major global health problem, especially in children, that remains incompletely understood and is not straightforward to treat. Furthermore, the changes in iron metabolism during a malaria infection may modulate susceptibility to coinfections. The release of heme and accumulation of iron in granulocytes may explain increased vulnerability to non-typhoidal Salmonella during malaria. The redistribution of iron away from hepatocytes and into macrophages may confer host resistance to superinfection, whereby blood-stage parasitemia prevents the development of a second liver-stage Plasmodium infection in the same organism. Key to understanding the pathophysiology of iron metabolism in malaria is the activity of the iron regulatory hormone hepcidin. Hepcidin is upregulated during blood-stage parasitemia and likely mediates much of the iron redistribution that accompanies disease. Understanding the regulation and role of hepcidin may offer new opportunities to combat malaria and formulate better approaches to treat anemia in the developing world.